(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the research field, network performance for different smart applications plays an important role in the IoT network. Several factors, such as packet delay, network throughput, energy consumption, heterogeneity, proper gateway placement and load balancing, have a greater impact on network performance. In this article, two factors, such as optimal gateway placement and energy consumption, are investigated in order to improve the performance of the IoT network. Various methods are used to find the lo-cation of the Coordinating Devices (CDs) and to place constraint gateways in such a way that all CDs within the network should be covered by at least one gateway in order to allow the dissemination of data within the net-work. All of these CDs in the wireless network send their data to their near-by gateway based on Euclidean distance optimization. Euclidean distance performance is better than linear data transmission. During data transmission, nodes are unable to transmit data due to obstacles encountered in the path to the destination which result in a minimal energy efficiency improvement. Our proposed system solves the issue of gateway location optimization based on different distance-based approaches called Euclidean Distance (ED) and Manhattan Distance (MD) used in the wireless network to achieve the objective of reducing energy consumption.